Examination of the psychometric characteristics of the Greek version of the Family Influence Scale in junior high school students - Harokopaki, Argyro; Tsigilis, Nikolaos; Zerva, Aikaterini-Kiriaki (Psychology: the Journal of the Hellenic Psychological Society, 2025)
This research was conducted to provide preliminary psychometric data for the Greek version of the Family Influence Scale (FIS). The FIS has been developed to assess the variety of ways family members may influence career decision making of its younger members. Data collection was based on designed self-report measures. 230 school pupils in the eighth and ninth grades, the research sample, were asked to provide information about their own behaviors or experiences by completing a brief demographic questionnaire, along with questionnaires on the Career Family Influence Scale, and the Life Satisfaction Scale. Construct validity, internal consistency, and reliability of the Greek version of FIS were validated by the data, making it suitable for research and clinical use in teenage Career Counseling. Apropos construct validity, findings confirmed its four main components: Financial Support, Informational Support, Family Expectations and Values/Beliefs. However, as to Values/Beliefs, the less robust component, findings involving older students should be interpreted cautiously until further study is conducted.